A kind of N-type battery conductive silver paste and preparation method thereof
By introducing AlPb-MOF material into the silver paste, the problems of low doping and poor contact performance of N-type silicon wafers are solved, and good contact between the silver paste and the silicon wafer surface and efficient electrical performance are achieved.
Patent Information
- Application Number
- CN202211247062.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-12
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-10-12
AI Technical Summary
The N-type silicon wafer is low in doping and insufficient doping uniformity, resulting in poor contact performance between the silver paste and the silicon wafer surface, increasing the contact resistance and damaging the open circuit voltage.
AlPb-MOF material is introduced into the silver paste, and its flexible porous structure is used to improve printing performance, and a good ohmic contact and open circuit voltage is formed through uniform mixing of lead and aluminum.
Good contact between the silver paste and the silicon wafer surface is achieved, contact resistance is reduced, and the stability of the open circuit voltage is improved.
Smart Images

Figure CN115410746B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a battery conductive silver paste, in particular to an N-type battery conductive silver paste and a preparation method thereof, belonging to the technical field of solar cell conductive silver paste. Background Art
[0002] Crystalline silicon solar cells have now developed into Perc-Se cell technology. Currently, the efficiency improvement means of this technology is mainly reflected in increasing the square resistance of silicon wafers, but the room for improvement is limited. In order to break through the technical bottleneck, N-type cell technology has been developed in recent years, mainly TOPCON cell technology and HJT cell technology. TOPCON cell technology has become a hot research topic in recent years due to its high equipment repetition rate with Perc-Se cell technology, low equipment investment cost, and easy switching. N-type silicon wafers have a large space for improving the photoelectric conversion efficiency of crystalline silicon solar cells due to their advantages of low photoinduced attenuation and long minority carrier lifetime, but it also brings a series of problems. N-type silicon wafers are low in doping, and the doping uniformity needs to be improved. This puts greater demands and challenges on silver paste.
[0003] The first thing to solve is the contact problem between the slurry and the silicon wafer surface. Aluminum has good contact performance, so aluminum powder is often introduced into TOPCON battery slurry to make silver-aluminum slurry, which can greatly improve the contact between the slurry and the silicon wafer and reduce the contact resistance. However, aluminum powder also has disadvantages: (1) Aluminum powder is lighter than silver powder and glass powder, and it is not easy to sink and contact the silicon wafer during sintering; (2) Aluminum powder is easily oxidized, making it inactive, and greatly reducing the conductivity of aluminum powder; (3) Silver powder and aluminum powder in the slurry form silver-aluminum thorns during the metallization process, which will cause the opening voltage to be lost. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a conductive silver paste for an N-type battery and a preparation method thereof. By introducing AlPb-MOF material into the silver paste, the flexible porous structure of the bimetallic AlPb-MOF material enables the silver paste to have good printing performance. During printing and sintering, the MOF organic material is burned out, while the remaining lead and aluminum are evenly mixed. Since lead is a heavy metal with a low melting point, the lead can bring the light aluminum melt to the surface of crystalline silicon to form a good ohmic contact. At the same time, the lead has good wettability, so that the aluminum can be evenly distributed on the surface of crystalline silicon to obtain a good open circuit voltage.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is specifically described as follows:
[0006] According to a first embodiment of the present invention, a conductive silver paste for an N-type battery is provided:
[0007] A conductive silver paste for an N-type battery, the conductive silver paste comprising:
[0008] The silver powder is 80-94 parts by weight, preferably 83-92 parts by weight, and more preferably 85-90 parts by weight.
[0009] Aluminum powder is 0.3-2.5 parts by weight, preferably 0.5-2 parts by weight, and more preferably 0.8-1.5 parts by weight.
[0010] The AlPb-MOF material is 0.2-2 parts by weight, preferably 0.3-1.8 parts by weight, and more preferably 0.5-1.5 parts by weight.
[0011] The organic carrier is 3-12 parts by weight, preferably 4-10 parts by weight, and more preferably 5-9 parts by weight.
[0012] The glass powder is 0.5-5 parts by weight, preferably 0.8-4.5 parts by weight, and more preferably 1-4 parts by weight.
[0013] Preferably, the purity of the silver powder is not less than 99.9%, and the particle size D50 thereof is 0.3-3 μm, preferably 0.5-2.5 μm, and more preferably 0.8-2 μm.
[0014] Preferably, the purity of the aluminum powder is not less than 99.9%, and the particle size D50 thereof is 0.5-3 μm, preferably 0.8-2.5 μm, and more preferably 1-2 μm.
[0015] Preferably, the silver powder is coated silver powder, wherein the content of the coating agent is 0.1-1.2wt%, preferably 0.3-1wt%, and more preferably 0.5-0.8wt%.
[0016] Preferably, the aluminum powder is coated aluminum powder, wherein the content of the coating agent is 0.1-1wt%, preferably 0.2-0.8wt%, and more preferably 0.3-0.7wt%.
[0017] Preferably, the AlPb-MOF material is spherical, and its average particle size is 0.3-2.5 μm, preferably 0.5-2.2 μm, and more preferably 0.8-2 μm.
[0018] Preferably, the glass powder is lead-containing glass powder, the particle size D50 of the lead-containing glass powder is less than 5 μm, preferably the particle size D50 of the lead-containing glass powder is less than 4 μm, and more preferably the particle size D50 of the lead-containing glass powder is less than 3 μm.
[0019] Preferably, the organic carrier is a system using ethyl cellulose as resin.
[0020] Preferably, the viscosity of the conductive silver paste for N-type batteries is 60-130 kcps@50rpm, its fineness is less than 8 μm, and its solid content is 87-95 wt%. Preferably, the viscosity of the conductive silver paste for N-type batteries is 65-125 kcps@50rpm, its fineness is less than 7 μm, and its solid content is 89-94 wt%. More preferably, the viscosity of the conductive silver paste for N-type batteries is 70-120 kcps@50rpm, its fineness is less than 6 μm, and its solid content is 90-92 wt%.
[0021] According to a second embodiment of the present invention, a method for preparing a conductive silver paste for an N-type battery is provided:
[0022] A method for preparing a conductive silver paste for an N-type battery or a method for preparing a conductive silver paste for an N-type battery according to the first embodiment, the method comprising the following steps:
[0023] 1) Dissolve an aluminum source, a lead source and terephthalic acid in deionized water to obtain a suspension, and then transfer the suspension to a reactor and heat it for reaction. When the reaction is completed, the AlPb-MOF material is obtained.
[0024] 2) First, the AlPb-MOF material, silver powder, aluminum powder, organic carrier and glass powder obtained in step 1) are uniformly mixed according to a proportion to obtain a premixed slurry, and then the premixed slurry is centrifuged to obtain a mixed slurry.
[0025] 3) Grinding the mixed slurry obtained in step 2), and filtering it after grinding to obtain the conductive silver paste for N-type batteries.
[0026] Preferably, in step 1), the aluminum source is aluminum nitrate and / or aluminum chloride. The lead source is lead nitrate and / or lead acetate. The mass ratio of the aluminum source, the lead source and the terephthalic acid added is 0.8-1.2:0.8-1.2:1-3, preferably 0.9-1.1:0.9-1.1:1.5-2.5.
[0027] Preferably, in step 1), the heating reaction is heating to 200-400° C. for 1-5 days, preferably heating to 240-350° C. for 2-4 days under sealed conditions.
[0028] Preferably, in step 2), the purity of the aluminum powder is not less than 99.9%, and the particle size D50 is 0.5-3 μm, preferably 0.8-2.5 μm, and more preferably 1-2 μm. The purity of the aluminum powder is not less than 99.9%, and the particle size D50 is 0.5-3 μm, preferably 0.8-2.5 μm, and more preferably 1-2 μm.
[0029] Preferably, in step 2), the AlPb-MOF material is spherical, and its average particle size is 0.3-2.5 μm, preferably 0.5-2.2 μm, and more preferably 0.8-2 μm.
[0030] Preferably, in step 2), the glass powder is lead-containing glass powder, the particle size D50 of the lead-containing glass powder is less than 5 μm, preferably the particle size D50 of the lead-containing glass powder is less than 4 μm, and more preferably the particle size D50 of the lead-containing glass powder is less than 3 μm.
[0031] Preferably, in step 2), the organic carrier is a system using ethyl cellulose as resin.
[0032] Preferably, in step 2), the silver powder is coated silver powder, wherein the content of the coating agent is 0.1-1.2wt%, preferably 0.3-1wt%, and more preferably 0.5-0.8wt%.
[0033] Preferably, in step 2), the aluminum powder is coated aluminum powder, wherein the content of the coating agent is 0.1-1wt%, preferably 0.2-0.8wt%, and more preferably 0.3-0.7wt%.
[0034] Preferably, the speed of the centrifugal treatment in step 2) is 850-1200 r / min, and the time of the centrifugal treatment is 35-100 s. Preferably, the speed of the centrifugal treatment is 900-1150 r / min, and the time of the centrifugal treatment is 45-80 s.
[0035] Preferably, the grinding treatment in step 3) is to grind the mixed slurry with a three-roll grinder for 4-12 times, preferably 5-10 times, and more preferably 6-9 times.
[0036] Preferably, the pore size of the filter during the filtration treatment in step 3) is 250-500 mesh, preferably 300-480 mesh, and more preferably 350-450 mesh.
[0037] Preferably, in step 2), the mixed addition amounts of the raw materials are as follows:
[0038] The silver powder is 80-94 parts by weight, preferably 83-92 parts by weight, and more preferably 85-90 parts by weight.
[0039] Aluminum powder is 0.3-2.5 parts by weight, preferably 0.5-2 parts by weight, and more preferably 0.8-1.5 parts by weight.
[0040] The AlPb-MOF material is 0.2-2 parts by weight, preferably 0.3-1.8 parts by weight, and more preferably 0.5-1.5 parts by weight.
[0041] The organic carrier is 3-12 parts by weight, preferably 4-10 parts by weight, and more preferably 5-9 parts by weight.
[0042] The glass powder is 0.5-5 parts by weight, preferably 0.8-4.5 parts by weight, and more preferably 1-4 parts by weight.
[0043] In the prior art, aluminum powder is generally introduced into TOPCON battery paste to make silver-aluminum paste, thereby improving the contact between the paste and the silicon wafer and reducing the contact resistance. However, the introduction of aluminum powder at the same time has the following disadvantages: (1) aluminum powder is lighter than silver powder and glass powder, and is not easy to sink and contact the silicon wafer during sintering; (2) aluminum powder is easily oxidized, making it inactive, and greatly reducing the conductivity of aluminum powder; (3) silver powder and aluminum powder in the paste form silver-aluminum spikes during the metallization process, which will cause the opening voltage to be lost.
[0044] In the present invention, a soluble aluminum salt and a soluble lead salt are reacted with phthalic acid to prepare a flexible and porous spherical AlPb-MOF material. The AlPb-MOF material is introduced into the silver paste. Due to the flexible porous structure of the bimetallic AlPb-MOF material, the silver paste has good printing performance. During printing and sintering, the MOF organic material is burned out, and the remaining lead and aluminum are evenly mixed. Since lead is a heavy metal with a low melting point, the lead can bring the light aluminum melt to the surface of crystalline silicon to form a good ohmic contact. At the same time, the lead has good wettability, so that the aluminum can be evenly distributed on the surface of crystalline silicon to obtain a good open circuit voltage.
[0045] In the present invention, the silver powder and aluminum powder are both coated powders, which can be directly purchased from the market. In the coated silver powder, the content of the coating agent accounts for 0.1-1.2wt% of the total mass of the coated silver powder. In the coated aluminum powder, the content of the coating agent accounts for 0.1-1wt% of the total mass of the coated aluminum powder.
[0046] In the present invention, the glass powder is lead-containing glass powder, which has low melting point, good wettability, uniform distribution, and easy control of etching the silicon nitride layer on the surface of crystalline silicon. All lead-containing glass powders of the present invention can be directly purchased from the market.
[0047] In the present invention, the organic carrier is a system with ethyl cellulose as the resin, which has good lubrication and film-forming properties and is easy to prepare products with different molecular weights to meet customer needs.
[0048] Compared with the prior art, the beneficial technical effects of the present invention are as follows:
[0049] 1: The N-type battery conductive silver paste of the present invention introduces AlPb-MOF material into the silver paste. The flexible porous structure of the bimetallic AlPb-MOF material enables the silver paste to have good printing performance, which can promote the uniform mixing of lead and aluminum during printing and sintering, and the lead can bring the lightweight aluminum melt to the surface of crystalline silicon to form a good ohmic contact. At the same time, the lead has good wettability, which can make the aluminum evenly distributed on the surface of crystalline silicon to obtain a good open circuit voltage.
[0050] 2: The raw materials for preparing the conductive silver paste for N-type batteries in the present invention can be purchased from the market except for the AlPb-MOF material. The preparation method of the conductive silver paste for N-type batteries has the advantages of easy availability of raw materials and simple preparation process, and is suitable for large-scale production and application. The prepared conductive silver paste for batteries has the advantages of simple components, easy acquisition, excellent printing performance, perfect linear shape, and excellent conductive performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 This is a SEM image of the silicon wafer surface after metallization using dilute nitric acid to etch the silver paste (Example 1).
[0052] Figure 2 This is a SEM image of the silicon wafer surface after metallization using dilute nitric acid to etch the silver paste (Example 2).
[0053] Figure 3 This is a SEM image of the silicon wafer surface after metallization using dilute nitric acid to etch the silver paste (Comparative Example 1).
[0054] Figure 4 This is an EL graph after the cell printed with the silver paste in Example 1 is tested using an EL tester.
[0055] Figure 5 This is an EL graph after the cell printed with the silver paste in Example 2 is tested using an EL tester.
[0056] Figure 6 This is an EL graph after the cell printed with the silver paste in Comparative Example 1 was tested using an EL tester. DETAILED DESCRIPTION
[0057] The technical solution of the present invention is illustrated below by way of example, and the scope of protection requested by the present invention includes but is not limited to the following embodiments.
[0058] A method for preparing conductive silver paste for N-type batteries, the method comprising the following steps:
[0059] 1) Dissolve an aluminum source, a lead source and terephthalic acid in deionized water to obtain a suspension, and then transfer the suspension to a reactor and heat it for reaction. When the reaction is completed, the AlPb-MOF material is obtained.
[0060] 2) First, the AlPb-MOF material, silver powder, aluminum powder, organic carrier and glass powder obtained in step 1) are uniformly mixed according to a proportion to obtain a premixed slurry, and then the premixed slurry is centrifuged to obtain a mixed slurry.
[0061] 3) Grinding the mixed slurry obtained in step 2), and filtering it after grinding to obtain the conductive silver paste for N-type batteries.
[0062] Preferably, in step 1), the aluminum source is aluminum nitrate and / or aluminum chloride. The lead source is lead nitrate and / or lead acetate. The mass ratio of the aluminum source, the lead source and the terephthalic acid added is 0.8-1.2:0.8-1.2:1-3, preferably 0.9-1.1:0.9-1.1:1.5-2.5.
[0063] Preferably, in step 1), the heating reaction is heating to 200-400° C. for 1-5 days, preferably heating to 240-350° C. for 2-4 days under sealed conditions.
[0064] Preferably, in step 2), the purity of the aluminum powder is not less than 99.9%, and the particle size D50 is 0.5-3 μm, preferably 0.8-2.5 μm, and more preferably 1-2 μm. The purity of the aluminum powder is not less than 99.9%, and the particle size D50 is 0.5-3 μm, preferably 0.8-2.5 μm, and more preferably 1-2 μm.
[0065] Preferably, in step 2), the AlPb-MOF material is spherical, and its average particle size is 0.3-2.5 μm, preferably 0.5-2.2 μm, and more preferably 0.8-2 μm.
[0066] Preferably, in step 2), the glass powder is lead-containing glass powder, the particle size D50 of the lead-containing glass powder is less than 5 μm, preferably the particle size D50 of the lead-containing glass powder is less than 4 μm, and more preferably the particle size D50 of the lead-containing glass powder is less than 3 μm.
[0067] Preferably, in step 2), the organic carrier is a system using ethyl cellulose as resin.
[0068] Preferably, in step 2), the silver powder is coated silver powder, wherein the content of the coating agent is 0.1-1.2wt%, preferably 0.3-1wt%, and more preferably 0.5-0.8wt%.
[0069] Preferably, in step 2), the aluminum powder is coated aluminum powder, wherein the content of the coating agent is 0.1-1wt%, preferably 0.2-0.8wt%, and more preferably 0.3-0.7wt%.
[0070] Preferably, the speed of the centrifugal treatment in step 2) is 850-1200 r / min, and the time of the centrifugal treatment is 35-100 s. Preferably, the speed of the centrifugal treatment is 900-1150 r / min, and the time of the centrifugal treatment is 45-80 s.
[0071] Preferably, the grinding treatment in step 3) is to grind the mixed slurry with a three-roll grinder for 4-12 times, preferably 5-10 times, and more preferably 6-9 times.
[0072] Preferably, the pore size of the filter during the filtration treatment in step 3) is 250-500 mesh, preferably 300-480 mesh, and more preferably 350-450 mesh.
[0073] Preferably, in step 2), the mixed addition amounts of the raw materials are as follows:
[0074] The silver powder is 80-94 parts by weight, preferably 83-92 parts by weight, and more preferably 85-90 parts by weight.
[0075] Aluminum powder is 0.3-2.5 parts by weight, preferably 0.5-2 parts by weight, and more preferably 0.8-1.5 parts by weight.
[0076] The AlPb-MOF material is 0.2-2 parts by weight, preferably 0.3-1.8 parts by weight, and more preferably 0.5-1.5 parts by weight.
[0077] The organic carrier is 3-12 parts by weight, preferably 4-10 parts by weight, and more preferably 5-9 parts by weight.
[0078] The glass powder is 0.5-5 parts by weight, preferably 0.8-4.5 parts by weight, and more preferably 1-4 parts by weight.
[0079] Example 1
[0080] Preparation of AlPb-MOF material: 1 part of aluminum nitrate, 1 part of lead nitrate and 2 parts of terephthalic acid were dissolved in 40 ml of deionized water to obtain a suspension, which was then transferred to a stainless steel crystallization kettle lined with polytetrafluoroethylene for sealing, and then placed in an oven at 280°C for reaction for 80 hours. After the reaction, the product was cooled to room temperature, and the obtained white precipitate was filtered and washed, and then placed in a 70°C oven for drying for 6 hours to obtain the AlPb-MOF material.
[0081] 88.3 parts of coated silver powder (silver powder purity is 99.9wt%, coating agent content is 0.8wt%, and its particle size D50 is 1.3μm), 1.2 parts of coated aluminum powder (aluminum powder purity is 99.9wt%, coating agent content is 0.6wt%, and its particle size D50 is 1.5μm), 0.5 parts of AlPb-MOF material, 2.1 parts of lead glass powder (D50<3μm) and 7.9 parts of organic carrier are stirred and mixed to obtain a premixed slurry, and then the premixed slurry is placed in a high-speed centrifugal disperser for centrifugal treatment (speed is 1000r / min, centrifugal time is 50s) to obtain a mixed slurry. Finally, a three-roll mill is used to grind the obtained mixed slurry 8 times (three-roll milling parameters are set as shown in Table 1), and after grinding, a 400-mesh filter is used for filtering to obtain a conductive silver paste for N-type batteries with a viscosity of about 96kcps@50rpm, a fineness of less than 6μm, and a solid content of about 91.2%.
[0082] Table 1
[0083] Three roller passes Back spacing / μm Front spacing / μm 1 80 40 2 40 20 3 20 10 4 20 10 5 15 7 6 15 7 7 10 5 8 10 5
[0084] Example 2
[0085] Preparation of AlPb-MOF material: 1 part of aluminum nitrate, 1 part of lead nitrate and 2 parts of terephthalic acid were dissolved in 40 ml of deionized water to obtain a suspension, which was then transferred to a stainless steel crystallization kettle lined with polytetrafluoroethylene for sealing, and then placed in an oven at 280°C for reaction for 80 hours. After the reaction, the product was cooled to room temperature, and the obtained white precipitate was filtered and washed, and then placed in a 70°C oven for drying for 6 hours to obtain the AlPb-MOF material.
[0086] 87.8 parts of coated silver powder (silver powder purity is 99.9wt%, coating agent content is 0.8wt%, and its particle size D50 is 1.3μm), 1.2 parts of coated aluminum powder (aluminum powder purity is 99.9wt%, coating agent content is 0.6wt%, and its particle size D50 is 1.5μm), 1.0 parts of AlPb-MOF material, 2.1 parts of lead glass powder (D50<3μm) and 7.9 parts of organic carrier are stirred and mixed to obtain a premixed slurry, and then the premixed slurry is placed in a high-speed centrifugal disperser for centrifugal treatment (speed is 1000r / min, centrifugal time is 50s) to obtain a mixed slurry. Finally, a three-roll grinder is used to grind the obtained mixed slurry 8 times (three-roll grinding parameters are set the same as in Example 1), and after grinding, a 400-mesh filter screen is used for filtering to obtain a conductive silver paste for N-type batteries with a viscosity of about 92kcps@50rpm, a fineness of less than 6μm, and a solid content of about 90.8%.
[0087] Example 3
[0088] Preparation of AlPb-MOF material: 1 part of aluminum nitrate, 1 part of lead nitrate and 2 parts of terephthalic acid were dissolved in 40 ml of deionized water to obtain a suspension, which was then transferred to a stainless steel crystallization kettle lined with polytetrafluoroethylene for sealing, and then placed in an oven at 280°C for reaction for 80 hours. After the reaction, the product was cooled to room temperature, and the obtained white precipitate was filtered and washed, and then placed in a 70°C oven for drying for 6 hours to obtain the AlPb-MOF material.
[0089] 87.3 parts of coated silver powder (silver powder purity is 99.9wt%, coating agent content is 0.8wt%, and its particle size D50 is 1.3μm), 1.2 parts of coated aluminum powder (aluminum powder purity is 99.9wt%, coating agent content is 0.6wt%, and its particle size D50 is 1.5μm), 1.5 parts of AlPb-MOF material, 2.1 parts of lead glass powder (D50<3μm) and 7.9 parts of organic carrier are stirred and mixed to obtain a premixed slurry, and then the premixed slurry is placed in a high-speed centrifugal disperser for centrifugal treatment (speed is 1000r / min, centrifugal time is 50s) to obtain a mixed slurry. Finally, a three-roll grinder is used to grind the obtained mixed slurry 8 times (three-roll grinding parameters are set the same as in Example 1), and after grinding, a 400-mesh filter screen is used for filtering to obtain a conductive silver paste for N-type batteries with a viscosity of about 88kcps@50rpm, a fineness of less than 6μm, and a solid content of about 88.8%.
[0090] Example 4
[0091] Preparation of AlPb-MOF material: 1 part of aluminum nitrate, 1 part of lead nitrate and 2 parts of terephthalic acid were dissolved in 40 ml of deionized water to obtain a suspension, which was then transferred to a stainless steel crystallization kettle lined with polytetrafluoroethylene for sealing, and then placed in an oven at 280°C for reaction for 80 hours. After the reaction, the product was cooled to room temperature, and the obtained white precipitate was filtered and washed, and then placed in a 70°C oven for drying for 6 hours to obtain the AlPb-MOF material.
[0092] 88.5 parts of coated silver powder (silver powder purity is 99.9wt%, coating agent content is 0.8wt%, and its particle size D50 is 1.3μm), 1.2 parts of coated aluminum powder (aluminum powder purity is 99.9wt%, coating agent content is 0.6wt%, and its particle size D50 is 1.5μm), 0.3 parts of AlPb-MOF material, 2.1 parts of lead glass powder (D50<3μm) and 7.9 parts of organic carrier are stirred and mixed to obtain a premixed slurry, and then the premixed slurry is placed in a high-speed centrifugal disperser for centrifugal treatment (speed is 1000r / min, centrifugal time is 50s) to obtain a mixed slurry. Finally, a three-roll mill is used to grind the obtained mixed slurry 8 times (three-roll milling parameters are set as shown in Table 1), and after grinding, a 400-mesh filter is used for filtering to obtain a conductive silver paste for N-type batteries with a viscosity of about 90kcps@50rpm, a fineness of less than 6μm, and a solid content of about 89.4%.
[0093] Example 5
[0094] Preparation of AlPb-MOF material: 1 part of aluminum nitrate, 1 part of lead nitrate and 2 parts of terephthalic acid were dissolved in 40 ml of deionized water to obtain a suspension, and then the suspension was transferred to a stainless steel crystallization kettle lined with polytetrafluoroethylene for sealing, and then placed in an oven at 300°C for reaction for 100 hours. After the reaction, the product was cooled to room temperature, and the obtained white precipitate was filtered and washed, and then placed in a 70°C oven for drying for 7 hours to obtain AlPb-MOF material.
[0095] 88.3 parts of coated silver powder (silver powder purity is 99.9wt%, coating agent content is 0.8wt%, and its particle size D50 is 1.3μm), 1.2 parts of coated aluminum powder (aluminum powder purity is 99.9wt%, coating agent content is 0.6wt%, and its particle size D50 is 1.5μm), 0.5 parts of AlPb-MOF material, 2.1 parts of lead glass powder (D50<3μm) and 7.9 parts of organic carrier are stirred and mixed to obtain a premixed slurry, and then the premixed slurry is placed in a high-speed centrifugal disperser for centrifugal treatment (speed is 1100r / min, centrifugal time is 50s) to obtain a mixed slurry. Finally, a three-roll grinder is used to grind the obtained mixed slurry 8 times (three-roll grinding parameters are set the same as in Example 1), and after grinding, a 400-mesh filter screen is used for filtering to obtain a conductive silver paste for N-type batteries with a viscosity of about 92kcps@50rpm, a fineness of less than 6μm, and a solid content of about 90.3%.
[0096] Comparative Example 1
[0097] 88.8 parts of coated silver powder (silver powder purity is 99.9wt%, coating agent content is 0.8wt%, and its particle size D50 is 1.3μm), 1.2 parts of coated aluminum powder (aluminum powder purity is 99.9wt%, coating agent content is 0.6wt%, and its particle size D50 is 1.5μm), 2.1 parts of lead glass powder (D50<3μm) and 7.9 parts of organic carrier are stirred and mixed to obtain a premixed slurry, and then the premixed slurry is placed in a high-speed centrifugal disperser for centrifugal treatment (speed is 1000r / min, centrifugal time is 50s) to obtain a mixed slurry. Finally, a three-roll mill is used to grind the obtained mixed slurry 8 times (three-roll milling parameters are set as shown in Table 1), and after grinding, a 400-mesh filter screen is used for filtering to obtain a conductive silver paste for N-type batteries with a viscosity of about 94kcps@50rpm, a fineness of less than 6μm, and a solid content of about 92.6%.
[0098] Comparative Example 2
[0099] Preparation of Al-MOF material: 1 part of aluminum nitrate and 2 parts of terephthalic acid were dissolved in 40 ml of deionized water to obtain a suspension, which was then transferred to a stainless steel crystallization kettle lined with polytetrafluoroethylene and sealed, and then placed in an oven at 280°C for 80 hours. After the reaction, the product was cooled to room temperature, and the obtained white precipitate was filtered, washed, and dried in an oven at 70°C for 6 hours to obtain the Al-MOF material.
[0100] 88.3 parts of coated silver powder (silver powder purity is 99.9wt%, coating agent content is 0.8wt%, and its particle size D50 is 1.3μm), 1.2 parts of coated aluminum powder (aluminum powder purity is 99.9wt%, coating agent content is 0.6wt%, and its particle size D50 is 1.5μm), 0.5 parts of Al-MOF material, 2.1 parts of lead glass powder (D50<3μm) and 7.9 parts of organic carrier are stirred and mixed to obtain a premixed slurry, and then the premixed slurry is placed in a high-speed centrifugal disperser for centrifugal treatment (speed is 1000r / min, centrifugal time is 50s) to obtain a mixed slurry. Finally, a three-roll mill is used to grind the obtained mixed slurry 8 times (three-roll milling parameters are set as shown in Table 1), and after grinding, a 400-mesh filter is used for filtering to obtain a conductive silver paste for N-type batteries with a viscosity of about 93kcps@50rpm, a fineness of less than 6μm, and a solid content of about 91.1%.
[0101] Comparative Example 3
[0102] Preparation of Pb-MOF material: 1 part of lead nitrate and 2 parts of terephthalic acid were dissolved in 40 ml of deionized water to obtain a suspension, which was then transferred to a stainless steel crystallization kettle lined with polytetrafluoroethylene and sealed, and then placed in an oven at 280°C for 80 hours. After the reaction, the product was cooled to room temperature, and the obtained white precipitate was filtered, washed, and dried in an oven at 70°C for 6 hours to obtain the Pb-MOF material.
[0103] 88.3 parts of coated silver powder (silver powder purity is 99.9wt%, coating agent content is 0.8wt%, and its particle size D50 is 1.3μm), 1.2 parts of coated aluminum powder (aluminum powder purity is 99.9wt%, coating agent content is 0.6wt%, and its particle size D50 is 1.5μm), 0.5 parts of Pb-MOF material, 2.1 parts of lead-containing glass powder (D50<3μm) and 7.9 parts of organic carrier are stirred and mixed to obtain a premixed slurry, and then the premixed slurry is placed in a high-speed centrifugal disperser for centrifugal treatment (speed is 1000r / min, centrifugal time is 50s) to obtain a mixed slurry. Finally, a three-roll mill is used to grind the obtained mixed slurry 8 times (three-roll milling parameters are set as shown in Table 1), and after grinding, a 400-mesh filter is used for filtering to obtain a conductive silver paste for N-type batteries with a viscosity of about 94kcps@50rpm, a fineness of less than 6μm, and a solid content of about 91.6%.
[0104] Performance Test:
[0105] The N-type cell conductive silver pastes prepared in Examples 1-5 and Comparative Examples 1-3 were printed onto crystalline silicon solar cells using a Maxwell screen printer, and then subjected to high-temperature sintering in a sintering furnace. The performance of each cell was tested.
[0106] The electrical performance data of the battery cell is tested using a Berger tester.
[0107] The electrical performance test data is shown in the following table:
[0108]
[0109]
[0110] It can be found from the above table that the conversion efficiency of the battery cells using the N-type battery conductive silver paste prepared by Examples 1-5 of the present application is significantly higher than the conversion efficiency of the battery cells using the N-type battery conductive silver paste prepared by Comparative Examples 1-3, and the conversion efficiency is improved by up to about 0.4% (in the prior art, even a 0.05% improvement in conversion efficiency is already a significant improvement).
[0111] The contact resistance of the printed line of the slurry was tested using a Kaslon TLM tester.
[0112] The test contact resistance data are as follows:
[0113]
[0114] It can be found from the above table that the contact resistance of the battery cells using the N-type battery conductive silver paste prepared by Examples 1-5 of the present application is significantly lower than the contact resistance of the battery cells using the N-type battery conductive silver paste prepared by Comparative Examples 1-3.
Claims
1. A conductive silver paste for N-type batteries, characterized by: The conductive silver paste comprises: 80-94 parts by weight of silver powder; 0.3-2.5 parts by weight of aluminum powder; 0.2-2 parts by weight of AlPb-MOF material; 3-12 parts by weight of organic carrier; and 0.5-5 parts by weight of glass powder. The AlPb-MOF material is prepared by the following method: dissolving an aluminum source, a lead source and terephthalic acid in deionized water to obtain a suspension, and then transferring the suspension to a reactor and heating it for reaction, and obtaining the AlPb-MOF material after the reaction is completed; wherein: the aluminum source is aluminum nitrate and / or aluminum chloride; the lead source is lead nitrate and / or lead acetate; the mass ratio of the added amounts of the aluminum source, the lead source and the terephthalic acid is 0.8-1.2:0.8-1.2:1-3; heating for reaction is heating to 200-400°C for reaction for 1-5 days.
2. The conductive silver paste for N-type battery according to claim 1, characterized in that: The conductive silver paste comprises: 83-92 parts by weight of silver powder; 0.5-2 parts by weight of aluminum powder; 0.3-1.8 parts by weight of AlPb-MOF material; 4-10 parts by weight of organic carrier; and 0.8-4.5 parts by weight of glass powder.
3. The conductive silver paste for N-type battery according to claim 1, characterized in that: The conductive silver paste comprises: 85-90 parts by weight of silver powder; 0.8-1.5 parts by weight of aluminum powder; 0.5-1.5 parts by weight of AlPb-MOF material; 5-9 parts by weight of organic carrier; and 1-4 parts by weight of glass powder.
4. The N-type battery conductive silver paste according to any one of claims 1 to 3, characterized in that: The purity of the silver powder is not less than 99.9%, and the particle size D50 is 0.3-3 μm; and / or The purity of the aluminum powder is not less than 99.9%, and the particle size D50 is 0.5-3 μm.
5. The conductive silver paste for N-type battery according to claim 4, characterized in that: The particle size D50 of the silver powder is 0.5-2.5 μm; and / or The particle size D50 of the aluminum powder is 0.8-2.5 μm.
6. The conductive silver paste for N-type battery according to claim 5, characterized in that: The particle size D50 of the silver powder is 0.8-2 μm; and / or The particle size D50 of the aluminum powder is 1-2 μm.
7. The conductive silver paste for N-type battery according to claim 4, characterized in that: The silver powder is coated silver powder, wherein the content of the coating agent is 0.1-1.2wt%; and / or The aluminum powder is coated aluminum powder, wherein the content of the coating agent is 0.1-1wt%.
8. The conductive silver paste for N-type battery according to claim 7, characterized in that: The content of the coating agent of the silver powder is 0.3-1wt%; and / or The content of the coating agent in the aluminum powder is 0.2-0.8wt%.
9. The conductive silver paste for N-type battery according to claim 8, characterized in that: The content of the coating agent of the silver powder is 0.5-0.8wt%; and / or The content of the coating agent in the aluminum powder is 0.3-0.7wt%.
10. The N-type battery conductive silver paste according to any one of claims 1-3 and 5-9, characterized in that: The AlPb-MOF material is spherical, and its average particle size is 0.3-2.5 μm; and / or The glass powder is lead-containing glass powder, and the particle size D50 of the lead-containing glass powder is less than 5 μm; and / or The organic carrier is a system using ethyl cellulose as resin.
11. The conductive silver paste for N-type battery according to claim 4, characterized in that: The AlPb-MOF material is spherical, and its average particle size is 0.3-2.5 μm; and / or The glass powder is lead-containing glass powder, and the particle size D50 of the lead-containing glass powder is less than 5 μm; and / or The organic carrier is a system using ethyl cellulose as resin.
12. The conductive silver paste for N-type battery according to claim 10, characterized in that: The average particle size of the AlPb-MOF material is 0.5-2.2 μm; and / or The particle size D50 of the lead-containing glass powder is less than 4 μm.
13. The conductive silver paste for N-type battery according to claim 11, characterized in that: The average particle size of the AlPb-MOF material is 0.5-2.2 μm; and / or The particle size D50 of the lead-containing glass powder is less than 4 μm.
14. The N-type battery conductive silver paste according to claim 12 or 13, characterized in that: The average particle size of the AlPb-MOF material is 0.8-2 μm; and / or The particle size D50 of the lead-containing glass powder is less than 3 μm.
15. The N-type battery conductive silver paste according to any one of claims 1-3, 5-9, 11-13, characterized in that: The viscosity of the N-type battery conductive silver paste is 60-130 kcps@50 rpm, its fineness is less than 8 μm, and its solid content is 87-95 wt %.
16. The conductive silver paste for N-type battery according to claim 15, characterized in that: The viscosity of the N-type battery conductive silver paste is 65-125 kcps@50 rpm, its fineness is less than 7 μm, and its solid content is 89-94 wt %.
17. The conductive silver paste for N-type battery according to claim 16, characterized in that: The viscosity of the N-type battery conductive silver paste is 70-120 kcps@50 rpm, its fineness is less than 6 μm, and its solid content is 90-92 wt %.
18. A method for preparing the conductive silver paste for N-type batteries as claimed in any one of claims 1 to 17, characterized in that: The method comprises the following steps: 1) Dissolve the aluminum source, lead source and terephthalic acid in deionized water to obtain a suspension, and then transfer the suspension to a reactor and heat it for reaction. After the reaction is completed, the AlPb-MOF material is obtained; 2) firstly, the AlPb-MOF material, silver powder, aluminum powder, organic carrier and glass powder obtained in step 1) are uniformly mixed according to a proportion to obtain a premixed slurry, and then the premixed slurry is centrifuged to obtain a mixed slurry; 3) Grinding the mixed slurry obtained in step 2) and filtering it after grinding to obtain the conductive silver paste for N-type batteries.
19. The method according to claim 18, characterized in that: In step 1), the aluminum source is aluminum nitrate and / or aluminum chloride; the lead source is lead nitrate and / or lead acetate; wherein the mass ratio of the aluminum source, the lead source and the terephthalic acid added is 0.8-1.2:0.8-1.2:1-3; and / or In step 1), the heating reaction is heating to 200-400° C. for 1-5 days.
20. The method according to claim 19, characterized in that: The mass ratio of the aluminum source, the lead source and the terephthalic acid added is 0.9-1.1:0.9-1.1:1.5-2.5; and / or In step 1), the heating reaction is heating to 240-350° C. under sealed conditions for 2-4 days.
21. The method according to any one of claims 18 to 20, characterized in that: The rotation speed of the centrifugal treatment in step 2) is 850-1200 r / min, and the time of the centrifugal treatment is 35-100 s; and / or The grinding treatment in step 3) is grinding the mixed slurry 4-12 times using a three-roll grinder; and / or The pore size of the filter during the filtration treatment in step 3) is 250-500 mesh.
22. The method according to claim 21, characterized in that: The centrifugal speed in step 2) is 900-1150 r / min; the centrifugal time is 45-80 s; and / or The grinding treatment in step 3) is grinding the mixed slurry 5-10 times using a three-roll grinder; and / or During the filtration treatment in step 3), the pore size of the filter is 300-480 meshes.
Citation Information
Patent Citations
Positive electrode material coated with porous oxide on surface and preparation method and application thereof
CN111048758A
Silver-aluminum paste for front fine grid of high-performance N-type solar cell and preparation method of silver-aluminum paste
CN113257457A